Machine and human roles for mitigation of misinformation harms during crises: An activity theory conceptualization and validation. (June 2023) - Tran, Thi; Valecha, Rohit; Rao, H. Raghav
Abstract: During crises, there is a need for a large amount of information in a short period. Such need creates the base for misinformation to spread within and outside the affected community. This may result in misinformation harms that can generate serious short term or long-term consequences. In such situations, there is a need for a joint human-machine effort to mitigate misinformation. Though there has been research in the area of management of AI in the recent past, there has been scarce work in examining situations where machines and humans interact for mitigating misinformation. In order to systematically analyze misinformation and suggest mechanisms for mitigation, we draw on Activity Theory to conceptualize a suitable framework. Such a framework will enable investigating human-machine interactions through loops of "misinformation generation" and "misinformation mitigation" activities for mitigating misinformation harms. The paper also validates the framework using three different target audiences, undergraduates, graduates and professionals. Highlights: A conceptual framework based on Third Generation Activity Theory for handling misinformation during humanitarian crises. The design is based on Machine and Human-based roles with interactions used for conceptualizing a Dual Activity System. Two contrasting views (1) Misinformation Generation Activity, and (2) Misinformation Mitigation Activity. Examination of one misinformation related case study and four misinformation scenarios.